Physical processes along the southern continental shelf and slope of Western Australia - Mohd Fadzil Mohd Akhir (University of Western Australia, 2012)
The circulation along the south coast of Western Australia was examined using field data and numerical modelling. Physical processes in this region, particularly along the continental shelf and slope regions, were poorly understood due to a paucity of field measurements.